Epidermal gene expression and ethnic pigmentation variations among individuals of Asian, European and African ancestry. Issue 10 (October 2014) - Yin, Lanlan; Coelho, Sergio G.; Ebsen, Dominik; Smuda, Christoph; Mahns, Andre; Miller, Sharon A.; Beer, Janusz Z.; Kolbe, Ludger; Hearing, Vincent J.
Abstract Differences in visible skin pigmentation give rise to the wide variation of skin colours seen in racial/ethnic populations. Skin pigmentation is important not only from cosmetic and psychological points of view, but more importantly because of its implications for the risk of all types of skin cancers, on photoaging, etc. Despite differences in those parameters in Caucasian and Asian skin types, they are remarkably similar in their production and distribution of melanins, and the mechanism(s) underlying their different characteristics have remained obscure. In this study, we used microarray analysis of skin suction blisters to investigate molecular differences underlying the determination of pigmentation in various skin types, and we used immunohistochemistry to validate the expression patterns of several interesting targets that were identified. Intriguingly, Caucasian and Asian skins had highly similar gene expression patterns that differed significantly from the pattern of African skin. The results of this study suggest the dynamic interactions of different types of cells in human skin that regulate its pigmentation, reveal that the known pigmentation genes have a limited contribution and uncover a new array of genes, including NINL and S100A4, that might be involved in that regulation.